Evaluation of 41 cases in term of inversion 9: Case reports - Yuce, Huseyin; Ozbey, Ulku; Etem, Ebru; Erol, Deniz; Deveci, Sukriye Derya; Ceylan, Gulay Gulec; Elyas, Halit (Ortadogu Ad Pres & Publ Co, 2008)
Human chromosome 9 with a pericentric inversion involving the qh region is considered normal. It has probably evolved through breakage and reunion and is retained through mendelian inheritance without any apparent phenotypic consequences. The incidence is reported to be about 1% to 1.65% in the general population. Despite being categorized as a minor chromosomal rearrangement, which does not correlate with abnormal phenotypes, many reports in the literature raised conflicting views regarding the association with subfertility and recurrent abortions, abnormal clinical conditions, as well as chromosomal abnormalities due to the possession of this inversion. We studied the incidence and clinical significance of 41 (1.42%) cases with inv(9) retrospectively from 2876 peripheral blood karyotypes collected over a 6-year period in the Department of Medical Biology and Genetic, Medical Faculty, Firat University. The significance of the inv(9) and the genetic counseling process was discussed in view of the literature.
Inversiyon 9 açisindan 41 olgunun de?erlendirilmesi
Keywords: cytogenetics; inversion; chromosome